Assessing ecosystem health following revegetation in the mountainous areas of northern China - Qu, Siyi; Wang, Shengping; Zhou, Fan; Li, Wenxin; Cai, Desheng; Zhang, Zhiqiang; Strauss, Peter; Wang, Kewen; Liu, Yiyao (Frontiers in Earth Science, 2025)
IntroductionAssessing ecosystem health and understanding its potential environmental controls are critically important for effective revegetation of mountainous areas where multiple agents may constrain ecosystem health and ecosystem usually fragiled accordingly.MethodsWe applied the VOR framework (vigor–organization–resilience model) to assess ecosystem health of a meso-scale mountainous watershed of northern China (Xiaoluan River watershed), and quantified environmental controls by integrating Ordinary Least Squares (OLS), Geographically Weighted Regression (GWR) and Multiscale Geographically Weighted Regression (MGWR) techniques.ResultsWith the proceeding of revegetation, ecosystem health of the watershed showed a slight improvement over 2006-2020 (p > 0.05), EHI (ecosystem health index) varied from 0.49 to 0.57, and the ecosystem resilience (ER) remained relatively low, with the mean ER over the years being only 0.19. Additionally, Moran's I showed strong spatially positive autocorrelations, especially for the plant functional types (PFTs) of NETT (Needleleaf evergreen tree, temperate) and BDTT (Broadleaf deciduous tree, temperate), indicative of a proneness to abrupt transition in case of an environmental perturbation. Both OLS and GWR (including MGWR) models suggested that thermal stress and water stress both are primary constraints on the ecosystem health of the watershed, and at seasonal scales, their controls alter by season, with T dominating in the beginning of growing season, whilst P dominates in growing season, well characterizing the major process controlling EHI of mountainous watersheds in transitional zone of northern China.DiscussionGiven intensified climate change and widespread revegetation, greater caution should be exercised when implementing large-scale afforestation in the region to avoid potential ecosystem collapse under environmental disturbances. Strategies to enhance resilience and adapt vegetation types to local hydrothermal conditions are recommended.